Analisis Vegetasi Penyusun Asmin Tropical Rain Forest Conservation 2, PT. Asmin Bara Bronang, Kapuas, Kalimantan Tengah - Suwito Setyo Budi; Agus Prijono; Karti Rahayu Kusumaningsih (Jurnal Wana Tropika, 2023)
Asmin Tropical Rain Forest Conservation 2 is a tropical natural forest which is a conservation area of ​​PT Asmin Bronang Kapuas, Central Kalimantan. The designation of new areas was carried out in 2018 and there was no research in the area that required data collection on the types of constituents of the area. The purposes of this research were to determine species composition, species diversity index, species evenness index, species richness index, and species dominance index. The method used in this study was collecting data on plants in area of ​​54.6 hectares with a sampling intensity of 1% using the Uniform Systematic Distribution Sampling with Random Start pattern. There are   14 plots in the form of nested samples with designations for 4 levels of plants (seedlings, saplings, poles, and trees). Results of the research showed that vegetation species composition was dominated by Shorea smithiana (Mahambung) of the Dipterocarpaceae family. Shorea parvifolia (Red Meranti), Euzyderoxylon zwageri (Ulin), Shorea smithiana (Mahambung), Mezzetia parviflora (Pisang-pisang), Syzygium spp. (Jambu-jambu), and Memecylon sumatrense (Kamasulan) are the 6 species that have the best regeneration rate, which are found at all plant levels. The highest IVI was Shorea smithiana (Mahambung) at the seedling was 46.55, pole 55.68, and tree 32.02 levels. At the sapling level, the highest IVI was Baccaurea bracteata Muell (Rambai forest) was 28.76. The species diversity index from seedling to pole level was moderate. At the tree level, the species diversity index was high (3.23). Species evenness index from seedling to tree level including height (0.82-0.92). The species richness index from seedling to pole was moderate. At the tree level, the species diversity index was high (7.45). The species dominance index of all levels was included in the low category (0.05-0.15).